An overview of development of sustainable agriculture in Lithuania - Mierauskas, Pranas (International Conference “Environmental Engineering”, 2020)
The purpose of this review paper is to analyse and evaluate the development of sustainable agriculture in Lithuania from 1990 to the present and to evaluate possibilities, willingness and motivation of farmers to participate in sustainable agriculture. It was established that sustainable agriculture developed from environmentally friendly agriculture and later from organic agriculture. Initially, organic agriculture prevailed and included compliance with environmental requirements; however, later it incorporated social and economic approaches as well. This paper analyses the organic farming practices that stimulated the development of sustainable agriculture. Agri-environmental agriculture has been found to be more popular with farmers as it provides compensatory payments and requires basic environmental knowledge. This work compares farmers’ motivation to participate not only in agri-environmental measures, but also in sustainable agriculture. Noteworthy, agri-environmental measures also have elements of sustainable development. The work compares the results of previous research on farmers’ motivation and willingness to participate in environmentally friendly farming measures. The research reveals that participation in voluntary programmes has to be economically encouraged. The main findings are as follows: sustainable agriculture developed from organic agriculture gradually by integrating principles of sustainable development; the results of comparative analysis discovered that farmers with deeper understanding of environmental protection are more motivated to implement farming that relies on sustainable agriculture approaches. The research is based on analysis and evaluation through such methods as descriptive and comparative data analysis in previous and recent periods and questionnaire based data collection in order to evaluate new types of farming.
Keywords: sustainable agriculture; organic farming; farmers; agrarian environment; sustainable development; environmental protection